New View of Low-Temperature Sintering Phenomenon of Nanometer-Size Particles Based on Molecular Dynamics Study. Issue 30 (10th May 2016) - Matsubara, Norie; Munetoh, Shinji; Furukimi, Osamu
ABSTRACT: In this study, we have investigated a behavior of particle with diameter several ten nanometers size at the time of heating on an atomic scale by numerical analysis using the molecular dynamics (MD) simulation. On solving the equation of motion, the Langevin equation was adopted. The Finnis-Sinclair potential, which can well reproduce the mechanical properties of a BCC-metal, was used as the interatomic force. We determined the relationship between the melting point (Tm ) of the nano-sized particles and its diameter by MD simulations. We have also investigated the self-diffusion coefficient of each atom-forming at a temperature larger or less than Tm of the submicron-size metal particles . As a result, even in case of heating at a temperature larger than Tm, the mean self-diffusion coefficient at the center of a particle was 10 -7 –10 -6 cm 2 /sec. On the other hand, at the surface layer of the particle was two to three orders of magnitude larger than that at the center. Those particles were in a quasi-molten state. It is conceivable that the thickness of the surface layer can explain a phenomenon that sintering progresses as the heating temperature increases.